2013
DOI: 10.1089/end.2013.0084
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Laparoscopic Radical Cystectomy for the Treatment of Bladder Cancer

Abstract: In experienced hands, LRC is a feasible and safe alternative to ORC with less blood loss, transfusion and analgesic requirement, shorter lengths of hospital stay, and less complications. LRC does, however, have longer operative times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
5
22
0
3
Order By: Relevance
“…The survival rate of LRC in the present study was almost comparable to that of MIRC (LRC or RARC) or that of ORC, as previously reported . In accordance with our results, systemic reviews and recent randomized trials for RARC have shown that oncological outcomes of MIRC are equivalent to those of ORC . Similar to previous reports, 5‐year relapse‐free survival, cancer‐specific survival and overall survival were stratified into pT and pN, and the presence or absence of lymph node dissection, pT and pN were significant factors associated with recurrence on multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The survival rate of LRC in the present study was almost comparable to that of MIRC (LRC or RARC) or that of ORC, as previously reported . In accordance with our results, systemic reviews and recent randomized trials for RARC have shown that oncological outcomes of MIRC are equivalent to those of ORC . Similar to previous reports, 5‐year relapse‐free survival, cancer‐specific survival and overall survival were stratified into pT and pN, and the presence or absence of lymph node dissection, pT and pN were significant factors associated with recurrence on multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Radical cystectomy is a standard treatment for locally muscle‐invasive bladder cancer and aggressive, non‐muscle‐invasive bladder cancer that is refractory to conservative treatment, but it is associated with a significant rate of complications . Therefore, MIRC, such as LRC and RARC, have been introduced to reduce postoperative complications . Indeed, MIRC is becoming popular for invasive and high‐grade bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that LRC was superior to ORC in perioperative outcomes, including EBL, blood transfusion rate, and analgesic requirement and there was no major difference in oncologic outcomes between LRC and ORC group. Tang et al [15] and Aboumarzouk et al [16] have also confirmed efficacy and safety of LRC by meta-analysis. With the continuous maturation of laparoscopic technology, robot-assisted radical cystectomy has become a treatment way for bladder cancer and its clinical feasibility has been recognized by more and more doctors [11].…”
Section: Discussionmentioning
confidence: 90%
“…9 Despite these limitations, this approach has been shown to be safe and effective in experienced hands. [10][11][12][13] Robotic surgery has recently gained popularity, threatening to replace select open and laparoscopic procedures. The purported advantages of robotic surgery over laparoscopic surgery are increased maneuverability, improved vision with ten times magnification, enhanced endo-wrist dexterity, tremor elimination, and a shorter learning curve.…”
Section: Introductionmentioning
confidence: 99%